2021
DOI: 10.3390/geriatrics6010030
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Support for Older Adults during the Initial Stages of the COVID-19 Pandemic: Results from a Geriatric Psychiatry Helpline

Abstract: Background. The COVID-19 pandemic and governmental lockdown measures disproportionally impact older adults. This study presents the results from a psychiatric helpline for older adults in Mannheim, Germany, during the lockdown, set up to provide information and psychosocial support. We aim to elucidate the needs of older adults, their reported changes, and the psychological impact during the initial stages of the health crisis. Methods: A total of 55 older adults called the psychiatric helpline between April a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Earlier studies suggested that younger people were more likely to be affected by the COVID-19 pandemic (7,11,13), and our study found that contacts by young people under 25 years increased throughout the study period, whereas contacts by people those older than 25 years gradually declined once the first lockdown lifted. In addition the number of over 65 year olds contacting services was smaller than by people under 65 years, similar to other studies (30).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Earlier studies suggested that younger people were more likely to be affected by the COVID-19 pandemic (7,11,13), and our study found that contacts by young people under 25 years increased throughout the study period, whereas contacts by people those older than 25 years gradually declined once the first lockdown lifted. In addition the number of over 65 year olds contacting services was smaller than by people under 65 years, similar to other studies (30).…”
Section: Discussionsupporting
confidence: 91%
“…Service providers reported that some callers were reluctant to overload their usual service providers, or some were having difficulty accessing these (20,21). From a qualitative perspective, providers attributed the increase in helpline demand between January 2020 and the end of March 2021 to COVID-19 related anxieties such as fears of infection, general anxiety about accessing healthcare, uncertainty about COVID-19 rules, questions about vaccination, and feelings of loss of control similar to other international studies (25,26,30,31) and observations in Brooks and colleagues rapid review (2020). Although, similar to the data from Greece and Malta (26,31), our qualitative results indicated potential increases in generalized anxiety; however, depression has not featured strongly in our data.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations